ETNOMATEMATIKA PADA TUTUP ARI GEDUNG KANTOR BUPATI TAPANULI SELATAN - Rahayu, Rina Sri (Program Studi Pendidikan Matematika Institut Pendidikan Tapanuli Selatan, 2024)
This research aims to determine the form or mathematical concept of the ornaments found on the Close Ari of the South Tapanuli Regent's Office Building. The decoration on the lid is one of the Mandailing cultural traditions that must be preserved because it contains its own meaning and significance in each form. We can find these ornaments in various areas in South Tapanuli, one of which is in South Tapanuli, specifically in the South Tapanuli Regent's Office Building. The decoration on the lid of the can is used as a medium for teaching mathematics in schools so that learning mathematics at school can begin by introducing local customs and culture. This article explores the mathematical ideas contained in the ornaments covering the South Tapanuli Regent's Office building. The discussion is descriptive, providing a detailed description of the ornaments. The results of the exploration and analysis of these ornaments found that there were mathematical concepts in the form of flat geometric shapes such as triangles, trapezoids, parallelograms, rhombuses, squares and rectangles. Keywords: Ornament; Close Ari; Ethnomathematics; Culture. This research aims to determine the form or mathematical concept of the ornaments found on the Close Ari of the South Tapanuli Regent's Office Building. The decoration on the lid is one of the Mandailing cultural traditions that must be preserved because it contains its own meaning and significance in each form. We can find these ornaments in various areas in South Tapanuli, one of which is in South Tapanuli, specifically in the South Tapanuli Regent's Office Building. The decoration on the lid of the can is used as a medium for teaching mathematics in schools so that learning mathematics at school can begin by introducing local customs and culture. This article explores the mathematical ideas contained in the ornaments covering the South Tapanuli Regent's Office building. The discussion is descriptive, providing a detailed description of the ornaments. The results of the exploration and analysis of these ornaments found that there were mathematical concepts in the form of flat geometric shapes such as triangles, trapezoids, parallelograms, rhombuses, squares and rectangles. Keywords: Ornament; Close Ari; Ethnomathematics; Culture.